(untitled) (Revista Científica Compendium, 2018)
Since its inception, the Tourist Destination Life Cycle Model (TDLCM), developed in 1980 by Richard Butler, led to great discussions and generated a vast literature focused on its application. The scrutiny, of which it has been object, has been extensive and its adaptations have been wide. In this work, through a bibliographical review, it is sought to establish the origin, conception and treatment, which has carried over more than three decades, in order to determine its validity as a strategic management and planning model within the field of tourism and its conceptual limitations.